LOW MOLECULAR WEIGHT BIODEGRADABLE POLYMER BASED NANOPARTICLES AS POTENTIAL DELIVERY SYSTEMS FOR THERAPEUTICS: THE WAY FORWARD? (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
A significant effort is underway to develop low molecular weight biodegradable polymer based nanoparticles as potential alternates for conventional high molecular weight biodegradable polymer based nanoparticles as delivery systems. Among the various options, low molecular weight biodegradable polymer based nanoparticles are attractive future delivery systems for nucleic acids, proteins and drugs due to their smaller particle size, higher solubility, higher permeability, higher association efficiency, better biodegradability, higher release efficiency, non haemolytic nature and lower cytotoxicity at normal physiological condition. In this current scenario, recent progresses on preparation techniques of Low Molecular Weight Biodegradable Polymer based nanoparticles and their therapeutic applications are focused in this review. However, there are significant remaining issues to practical applications, such as specific interactions of these low molecular weight biodegradable polymer based nanoparticles with human organs, tissue cells, resistant microbial cells, biomolecules, and metabolic fate. Hence, further deep research for overcoming these practical barriers may be pioneered a new avenue in the near future.